The impact of flexible working arrangements on competitive advantages of organization - Pavlova, Oksana (Vilnius University Open Series, 2019)
In modern marketplace business organizations are obliged to take into consideration that in order to compete among other organizations, they must attract the best talents who are able to make creative decisions. According to the latest issue of world competitiveness report (2019), employees are striving for flexibility despite the observed fact that they also tend to lack skills and described as volatile. Organizations are trying to suggest appealing working conditions in order to position themselves as attractive employees. This might be the reason why many of the leading organizations in the world position themselves as employers of flexible working conditions (Wiryakusuma, Chai, King et al. 2017). As there is a skills gap noticed as a prevailing global trend, it became harder for organizations to change employees. Therefore, a lot of efforts and investments are necessary in order to keep a skillful and efficient employee.